Successful treatment of sudden sensorineural hearing loss by means of pharmacotherapy combined with early hyperbaric oxygen therapy: Case report. Issue 51 (December 2017) - Olex-Zarychta, Dorota
Abstract: Rationale: According to the World Health Organization reports, adult-onset hearing loss is the 15th leading cause of burden of disease, and is projected to move up to 7th by the year 2030, especially in high-income countries. Sudden sensorineural hearing loss is considered by otologists as a true otologic emergency. The current standard treatment for sudden hearing loss is a tapered course of oral high-dose corticosteroids. The described clinical case points to the validity of undertaking early hyperbaric oxygenation (HBO) therapy together with corticosteroids for full recovery of adult onset idiopathic sudden sensorineural hearing loss. Patient concerns: A 44-year-old woman complained of an abrupt hearing deterioration in the left ear with the sensation of aural fullness and loud tinnitus presented for 48 hours. The patient was admitted to the Department of Otolaryngology of Public Hospital for diagnosis and treatment. Diagnoses: The patient was diagnosed with unilateral sudden idiopathic sensorineural hearing loss, assessed by measuring the tonal audiograms. Interventions: The patient received treatment including oral high-dose corticosteroids combined with HBO protocol including 15 daily 1-hour exposures to 100% oxygen at 2.5 atmosphere absolute. Outcomes: A pharmacotherapy combined with early HBO resulted in full recovery of hearing. Lessons: Early implementation of HBO to the pharmacotherapy in sudden sensorineural hearing loss may lead to full recovery of hearing. There is a need for systematic research to establish guidelines for optimal number of HBO sessions in relation to the timeframe from hearing loss symptoms onset to implementation of HBO therapy. Abstract : Supplemental Digital Content is available in the text